Androgen action in female reproductive physiology. Issue 3 (June 2016) - Walters, Kirsty A.; Simanainen, Ulla; Gibson, Douglas A.
Abstract : Purpose of review: In the last decade, it has been proven that androgens acting via the androgen receptor (AR) play an important role in the regulation of female reproductive function. However, the specific site of action and the precise pathways involved remain to be fully elucidated. This review aims to combine findings from emerging basic research to provide new insights into the roles of AR-mediated actions, and the mechanisms involved, in normal ovarian, uterine, and mammary gland function. Recent findings: Our understanding of the specific roles of androgens in females has been hindered as females with complete androgen insensitivity cannot be generated by natural breeding, and interpretation of results from pharmacological studies has led to confusion as some androgens can be converted into estrogens, which can mediate actions via estrogen receptors. However, with the creation of global and cell-specific female AR knockout mouse models by Cre-LoxP technology, and the use of aromatizable and nonaromatizable androgens, novel roles for androgens in the regulation of female reproductive physiology have been revealed. Summary: AR-mediated mechanisms play important roles in mediating normal ovarian, uterine, and mammary gland function and there is hope that further elucidation of the role of androgens in female reproductive physiology may translate into the development of novel, evidence-based, and targeted treatment for androgen-associated conditions.